Thoracic trauma review - de Carvalho, Bruno Mileno Magalhães; da Cunha, Tayana Conde; Coelho, Maria Fernanda Lobão Lima; Santos, Ivana Maria Batista; Trindade, Beatriz Rafaelly de Souza; Fróes, Geovanna Matos; Albino, Ana Luiza da Veiga; Neres, Barbara Cristina Rodrigues (Seven Editora, 2023)
The objective of this work is to demonstrate the clinical and epidemiological profile of thoracic trauma, analyzing its possible causes, medical management, patient profile, types of trauma and mortality through a literature review, selecting articles and other bibliographies from 2000 to 2022, using PUBMED and Google Scholar databases. Through the results, it was observed that thoracic injuries are among the main causes of death, violence, reflecting the increase in cases of accidents with a predominance of males. Specific care for thoracic injuries occurs through primary and secondary assessments according to the classification by degree of seriousness. In addition, the types of injuries are characterized by blunt, penetrating, transfixing, the highest risk such as pneumothorax, cardiac tamponade, hemothorax, flail chest and the more specific ones such as pulmonary contusion, costal fractures and heart injury. Thus, it is concluded that there are several types of trauma involving the thorax and that men are the most affected, thus observing the importance of seeking preventive measures for such cases. DOI: https://doi.org/10.56238/colleinternhealthscienv1-076